Industrial training report: Prism Integrated Sdn Bhd / Muhammad Nazir Abdul Aziz - Abdul Aziz, Muhammad Nazir (Perpustakaan Tengku Anis, 2019)
This academic report paper is made solely based from 1st February 2019 until 28th June 2019 during the period of internship in Operation Department, Prism Integrated Sdn Bhd. This report shows the student internship experiences and activities in Prism for about five months in this department. Plus, the student describe the reality of the company that serve its customers and how the company actually do it while maintaining the privacy and confidential of the client's asset. Industrial training or internship is a compulsory activity required for the 7th semester students to complete the studies in specific courses under the faculty of Information Management.